Molecular Characterization Analysis of Thalassemia and Hemoglobinopathy in Quanzhou, Southeast China: A Large-Scale Retrospective Study - Zhuang, Jianlong; Zhang, Na; Wang, Yuanbai; Zhang, Hegan; Zheng, Yu; Jiang, Yuying; Xie, Yingjun; Chen, Dongmei (Frontiers in Genetics, 2021)
Background: There are limited reports available on investigations into the molecular spectrum of thalassemia and hemoglobinopathy in Fujian province, Southeast China. Here, we aim to reveal the spectrum of the thalassemia mutation and hemoglobinopathy in Quanzhou prefecture, Fujian province. Methods: We collected data from a total of 17,407 subjects with the thalassemia trait in Quanzhou prefecture. Gap-PCR, DNA reverse dot blot hybridization, and DNA sequencing were utilized for common and rare thalassemia gene testing. Results: In our study, we identified 7,085 subjects who were carrying thalassemia mutations, representing a detection rate of 40.70% (7,085/17,407). Among them, 13 different α-thalassemia gene mutations were detected, with the most common mutation being –SEA (69.01%), followed by –α3.7 (21.34%) and –α4.2 (3.96%). We also discovered 26 β-thalassemia gene mutations, with the mutations of IVS-II-654 (C > T) (36.28%) and CD41/42(–TCTT) (29.16%) being the most prevalent. Besides, a variety of rare thalassemia variants were identified. Among them, the –FIL, βMalay, βIVS–I–130, and βIVS–II–672 mutations were identified in Fujian province for the first time. Additionally, we detected 78 cases of hemoglobinopathies, of which Hb Owari was the first reported case in Fujian province and Hb Miyashiro was the first case identified in the Chinese population. Conclusion: Our study indicates that there is a diverse range of thalassemia mutations, and it also reveals the mutation spectrum of rare thalassemia and hemoglobinopathies in Quanzhou, Fujian province. It provides valuable data for the prevention and control of thalassemia in Southeast China.